The Effect of the Number of Members of the Board of Directors who are Members of the Society of Certified Accountants on Reducing the Probability of Fraud in Companies with the Moderating Role of Audit Quality - Roohalah Seddighi; Jalal Doudkanloy Milan; Shiva Ebrahimi (پژوهش‌های تجربی حسابداری)
In this study, the effect of the number of certified accountants on the board of directors on reducing the likelihood of fraud in companies listed on the Tehran Stock Exchange, with audit quality as a moderating factor, was examined for the period from 2016 to 2018. The statistical population consisted of a sample of 116 companies observed over seven years, selected using the systematic elimination method based on specific criteria. A logistic regression model was employed to test the research hypotheses. The results of the hypothesis testing, conducted using the logistic regression model, indicate that the number of board members who are certified accountants has a significant negative effect on the probability of fraud in companies. In other words, a higher representation of certified accountants on the board is associated with a lower likelihood of corporate fraud. Additionally, audit quality, as a moderating variable, intensifies this effect. Therefore, it can be concluded that when more board members are certified accountants and the company is audited by institutions with a Grade A rating, the probability of fraud in companies is substantially reduced